Effect of curdlan on textural and cooking qualities of noodles made with tofu. Issue 8 (12th June 2018) - Xin, Yingji; Lee, Ji Y.; Kim, Jisuk; Kim, Yookyung
Abstract: This study developed the noodle from tofu. Tapioca starch and curdlan were added for improving texture and cooking quality. Tofu noodles were prepared with tapioca (50 g) (control), tapioca (20 g) and curdlan (5–7 g) (TC group), and curdlan (8–9 g) (C group). The viscosity decreased to control, TC and C, and both TC and C showed increasing capabilities as more curdlan was added. Cooking loss of TC (5.7–6.3%) or C (4.9–5.4%) was lower than that of the control (6.8%). C group showed the highest firmness which increased as more curdlan was added while TC and control showed similar results. Tensile strength of TC (2.3–2.7 N cm − 2 ) was higher than that of the control or C (2.0 N cm − 2 ). Our results revealed that curdlan can be used to lower the amount of tapioca starch during the process of making tofu noodles. Practical applications: Tofu processing was applied to develop a protein enhanced noodle. Curdlan, a thermogelable polysaccharide produced by bacteria, was evaluated to lower the amount of tapioca starch during the process of making tofu noodles. Our results suggest that tapioca starch can be completely replaced by curdlan. The thermoirreversible gel property of curdlan provides strong interactions among compositions of tofu noodles, resulting in improved textural and cooking properties of tofu noodles.